New record of the Greater grison (Galictis vittata) in the Northeast Sierra of Puebla, México - Lucas-Juárez , Gaudencio; Lucas-Juárez, Jesús David; Díaz-García, Juan M. (Therya Notes, 2021)
Despite its wide distribution throughout the American continent, the Greater grison (Galictis vittata) is one of the mammals with the fewest number of studies that report its presence or describe aspects of its ecology. In México, the Greater grison is an endangered species and is protected by the Mexican government. Knowing the distribution of this threatened species can help to design conservation strategies. Our aim was to describe a new record of the Greater grison in a heterogeneous landscape of the Northeast Sierra of Puebla, México. On October 24, 2020 around 12:00 hours, we found an individual of the Galictis vittata species in a shade-coffee plantation, located in a cloud forest landscape in Tuxtla, Puebla, México. This record of the Greater grison is the fourth known for the state of Puebla, México. Likewise, it broadens the distribution of the species 11.2 km southwest of the nearest locality, and occurs outside of their the range of potential distribution. We emphasize that this threatened species can move in riverside landscapes conformed by cloud forest, secondary vegetation, shade-coffee plantations, and agricultural crops traditionally managed by inhabitants of a tutunakú community.